Investigation for adhesion enhancement of hydroxyapatite coatings on Ti-12Cr alloy using the dipcoating method for orthopedic implant - Sanny Ardhy; Islahuddin Islahuddin; Meiki Eru Putra (Jurnal Polimesin, 2025)
Titanium and its alloys are extensively applied in biomedical due to their light weight, corrosion resistance, and biocompatibility. However, conventional alloys such as Ti-6Al-4V possess a high elastic modulus (~110 GPa), much greater than that of natural bone (10-30 GPa), leading to stress shielding and delayed bone healing. To overcome this limitation, Î²-type titanium alloys with lower modulus have been developed, including Ti-12Cr, which is intended for spinal fixation implants. Previous studies have reported frequent surface cracking in HA layers, potentially reducing implant durability. In this study, bio-HA derived from scales of ikan kakap putih (Lates calcarifer), an abundant fishery by-product, was applied as a coating suspension. The natural collagen present in the scales was expected to enhance coating adhesion. HA layers were deposited on Ti-12Cr substrates using dip coating with dipping times of 20, 24, 34, and 40 seconds. The results show that HA derived from scales of ikan kakap putih exhibits good coating adhesion strength. This improvement in adhesion helps minimize cracking in the HA layer. The highest adhesion was achieved at a dipping time of 20 s, with only 2% of the coated area peeling off. In addition, the dip-coating process produced thin and uniform HA layers, with surface coverage reaching 98.14% at a dipping time of 40 s. The improved adhesion of the HA coating is expected to enhance osseointegration and reduce implant inflammation effects in biomedical applications.